A New Erosion Model for Wind-Induced Structural Vibrations - Keqin Yan; Yi Zhang; Tao Cheng (Shock and Vibration)
In recent years, computational fluid dynamics (CFD) method has been widely utilized in simulating wind-induced snow drifting. In the simulating process, the erosion flux is the main controlling factor which can be calculated by the product of erosion coefficient and the differences between the flow stress and threshold stress. The erosion coefficient is often adopted as an empirical constant which is believed not to change with time and space. However, in reality, we do need to consider the influences of snow diameter, density, and wind speed on the erosion coefficient. In this technical note, a function of air density, sow particle density, snow particle radius, and snow particle strength bond is proposed for the erosion coefficient. Based on an experiment study, the effects of these parameters in erosion coefficient is analyzed and discussed. The probability distribution and value range of erosion coefficient are also presented in this technical note. The applicability of this approach is also demonstrated in a numerical study for predicting the snow distributions around a cube structure. The randomness of the structural vibrations is studied with details.